The Influence of Pandu Online Website Quality Toward User Satisfaction in Garut Regency Using Webqual 4.0 Method - Yulia, Hanna; Alamanda, Dini Turipanam; Ramdhani, Abdullah; Amalia, Vieny Marita; Mariam, Dinar (Department of Government Studies, Universitas Syiah Kuala, 2024)
The Pandu Online website provides benefits for the government in providing effective and efficient public services that enable the government to provide better accessibility for the community. This study aims to analyze the effect of the quality of the Pandu Online website on user satisfaction in Garut Regency using the Webqual 4.0 method. The Webqual 4.0 method is an approach that integrates advanced technologies such as artificial intelligence, big data analysis, Internet of Things (IoT), and others, to improve the quality and experience of users when accessing websites. This study uses a quantitative approach by conducting a survey of 100 Garut residents who are users of Pandu Online website. The collected data were analyzed using the Structural Equation Modelling - Partial Least Square (SEM PLS) with the help of WarpPLS 7.0 software. The results showed that there is an influence on usability, information quality, interaction service quality, which are the dimensions of website quality on user satisfaction. This research contributes to the application of the Webqual 4.0 method which can increase user satisfaction in the future.